Participation and Iterative Experiments: Designing Alternative Futures with Migrants and Service Providers - Alessandro Pollini; Alessandro Caforio (Social Sciences, 2021)
The current crisis of participation and crisis of engagement of Western societies also affects the application and the validity of the participatory design methodology. Traditional techniques to collaboratively design future solutions with the users and bring their knowledge to the technology application might not no longer be sufficient for the complex nature of our societies. This paper describes the applied research and design of a Digital Companion with AI-based profiling, needs matching, and service-access supporting chatbots. The objective of the Digital Companion is to enhance both the effectiveness of the services currently provided to migrants and refugees by local public administration and organizations, and the life quality of the migrants themselves. The adoption of participatory, iterative, and experimental co-creation approaches allowed to contribute to the innovation of the participatory design framework at a theoretical and methodological level, as is required in order to turn participation into action, to go beyond the mere public consultation and to find new pathways for involving all the citizens (not only migrants or local service providers) as a first step to build a successful project.